The Effects of the Recession on Attitudes toward Business Ethics: An Inter‐temporal Study of Business Students in 2001, 2009, and 2010. (1st March 2013) - Segal, Lydia; Haberfeld, Maria; Gideon, Lior
Abstract This inter‐temporal study compares the ethical attitudes of business students at three points: in 2001, when the economy was relatively healthy; in 2009, near the beginning of the current recession; and in 2010, when the economy was worse. Ethical attitudes were measured by replicating a popular survey consisting of 25 ethically charged vignettes. The survey measures willingness to engage in white‐collar crime behaviors, some clearly illegal; others marginally unethical. Findings show an increase in tolerance for clearly illegal behaviors from 2001 to 2009 and an increase in tolerance for an even broader array of unethical acts from 2009 to 2010. As compared with 2001 respondents, 2009 respondents were more tolerant of seriously illegal behaviors but less tolerant of marginally unethical ones. In 2010, respondents were more accepting of both kinds of unethical behaviors. The results also suggest that the change in ethical attitudes from 2009 to 2010 was larger than the average annual change in ethics from 2001 to 2009. These findings are discussed within the framework of classical strain theory, Agnew's General Strain Theory, and the legitimacy of social institutions.